Tributos municipais: um mecanismo de aplicação da política municipal e sua relação com os resultados eleitorais - Regatieri, Rebeca Regina (2013)
The present work studies the variable regarding to the tax revenue directly collected by municipalities. It highlights three objectives: i) to analyze the impact of constitutional transfers from the Municipal Participation Fund (MPF) on direct municipal tax revenues, ii) analyze the existence of a political cycle on the collection, and iii) analyze the impact of the collection on the current mayors's probability of reelection. The methodology used for the analysis of MPF on the municipal tax collection is the Regression Discontinuity (RD) in fuzzy design (Angrist & Pischke, 2008), using for this the MPF discontinuities due to changes in population groups. To analyze the political cycle, we use regressions of the municipal tax revenues variable on year dummies referring to the mayors's year administration, with fixed effects and according to the political cycles literature(Vine & Mattos, 2011; Araújo Leite Filho, 2010; Nakaguma & Bender 2010). Regarding the impact of the variable of interest on the incumbent mayors's probability of reelection, the estimation methodology follows three stages in the estimation of an OLS model (OLS), for the whole sample and to the vicinity of these discontinuities. The results indicate a both negative and increasing effect of MPF on municipal tax revenues, along cert a in population groups, suggesting that mayors would prefer cutting tax revenues, rather than simply use the granted additional transfers in order to increase the local public good. From this gap in municipal tax revenue allowed by MPF, we find the existence of political cycles, being the tax collections in the early years of the mandate above the tax collection in the election year. In respect to the impact on re-election, the results are not robust, indicating the necessity for information that detach the effect of increases in tax rates from the effects of increases in the tax base or improvements in the structure of municipal tax collection, which may be producing a more balanced or equitable municipal tax collection system.